Effects of Fiscal Stimulus in Structural Models - Kumhof, Michael (IMF Working Papers; Working Paper ;, 2010)
The paper assesses, using seven structural models used heavily by policymaking institutions, the effectiveness of temporary fiscal stimulus. Models can, more easily than empirical studies, account for differences between fiscal instruments, for differences between structural characteristics of the economy, and for monetary-fiscal policy interactions. Findings are: (i) There is substantial agreement across models on the sizes of fiscal multipliers. (ii) The sizes of spending and targeted transfers multipliers are large. (iii) Fiscal policy is most effective if it has some persistence and if monetary policy accommodates it. (iv) The perception of permanent fiscal stimulus leads to significantly lower initial multipliers.